12 Cardiac implantable electronic devices complications – a single centre experience. (7th October 2015) - Ryan, N; Mahon, N; Walsh, K; O'Neill, J; Keelan, E; Keelan, P; Galvin, J; Kuan, K
Abstract : Background: Indications for cardiac implantable electronic devices including pacemakers, cardiac resynchronization therapy and implantable cardiac defibrillators are increasingly expanding, however complications associated with these devices are associated with increased patient morbidity and healthcare consumption. Population based data from Denmark has shown a higher complication rate (9.5%) than previously identified in clinical trials. 1 Objectives: We aimed to assess our departmental complication rate for cardiac implantable electronic devices and conduct a cost analysis of our complications. Methods: A retrospective review all patients (n = 397) who underwent new implantation, upgrade or generator change of any cardiac implantable electronic device from January to December 2014 was carried out. Review of out-patient and in-patient records, together with review of Heart Rhythm Ireland data allowed completion of a standardised set of data elements for each patient. Statistical analysis was carried out using SPSS. Results: Baseline characteristics for our population are shown in Table 1 . Our overall complication rate was 10.83%, which is in keeping with the population based data from the Danish group Table 2 . Additional hospital bed days cost €187, 962. Conclusion: Our complication rate is higher than those reported in clinical trials, however is in keeping with the rates in the large Danish population based study. Cardiac implantable device complications lead to significant cost implications, with our data to date only accounting for the cost of hospital bed nights based on the most recent audited data from our institution. Further work will be carried out to assess the cost of investigations and procedures resulting from our cardiac implantable electronic device complications.